2018
DOI: 10.7567/jjap.57.032201
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear model analysis of all-optical flip-flop and inverter operations of microring laser

Abstract: We explore a theoretical model of bistability at two adjacent lasing wavelengths from an InGaAs/InGaAsP multiple quantum well (MQW) microring laser. We show that nonlinear effects on the phase and amplitude play significant roles in the lasing operations of the microring laser. Numerical simulations indicate that all-optical flip-flop operations and inverter operations can be observed within the same device by controlling the injection current. The validity of our analysis is confirmed by a comparison of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The principle of the all-optical flip-flop and inverter is based on the injection locking in the laser and the XGM between the main lasing wavelength and the adjacent one, as mentioned in Section II. We found that both operation modes are realized in the same microring laser [33] and proposed analysis model for the switching of operations without discriminating between CW and CCW lasing directions [34]. However, there are some discrepancies between the theoretical and experimental results.…”
Section: A Modelingmentioning
confidence: 89%
See 4 more Smart Citations
“…The principle of the all-optical flip-flop and inverter is based on the injection locking in the laser and the XGM between the main lasing wavelength and the adjacent one, as mentioned in Section II. We found that both operation modes are realized in the same microring laser [33] and proposed analysis model for the switching of operations without discriminating between CW and CCW lasing directions [34]. However, there are some discrepancies between the theoretical and experimental results.…”
Section: A Modelingmentioning
confidence: 89%
“…The basic principle of the proposed all-optical flip-flop and inverter devices is discussed in [33,34]. The flip-flop is operated by the injection locking at the resonant wavelength next to the main lasing wavelength in the microring laser.…”
Section: B Operation Principlementioning
confidence: 99%
See 3 more Smart Citations